Adenovectored RSV prefusion glycoprotein + soluble glycoprotein combination immunization establishes persistent opsonophagocytic antibody response through IgG3 - Tong, Xin; Blanc, Ross; Cizmeci, Deniz; Malca, Hadar; Kang, Jaewon; Comeaux, Christy; Callendret, Benoit; Bastian, Arangassery Rosemary; Khan, Mehak Zahoor; Alter, Galit; Lingwood, Daniel; McNamara, Ryan P. (Frontiers in Immunology, 2025)
IntroductionRespiratory syncytial virus (RSV) causes significant lower-respiratory-tract disease in high-risk groups. A phase IIb trial showed that a combination vaccine of Ad26-vectored prefusion RSV F (Ad26.preF) plus soluble prefusion F protein (SpreF) was 80 % protective, yet the longevity and functionality of these humoral responses are unknown.MethodsSera from vaccinated adults were analyzed 12 months after the primary dose and 28 days after a homologous booster at 1 year. IgG subclasses, isotypes, Fc-γ receptor (FcγR) binding, and Fc-dependent effector functions including opsinophagocytosis against RSV-F subtypes A and B were quantified via Systems Serology.ResultsA single dose generated durable immunity: IgG3-driven opsonophagocytic activity and broad FcγR engagement (via IgG1, IgG2, and IgG3) persisted through 12 months without appreciable decay. The booster did not increase antibody titres, FcγR binding, or functional activity, indicating that the primary response had already plateaued.DiscussionOne dose of Ad26.preF + SpreF elicits a long-lasting, functionally potent humoral response that is not further enhanced by a booster at 12 months, suggesting limited benefit from early re-vaccination. Continued follow-up will clarify the duration of protection and inform booster timing in vulnerable populations.